2011
DOI: 10.1111/j.1476-4431.2011.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis associated with septic peritonitis in a cat

Abstract: Ocular complications secondary to systemic sepsis are well documented in people but seldom reported in the veterinary literature. To the authors' knowledge this is the first report of uveitis linked to septic peritonitis in any veterinary species and the first to report sepsis-related uveitis in a cat. Ocular inflammatory disease in the context of critical illness deserves attention as a potential significant source of morbidity. The development of ocular inflammatory disease may serve as a sentinel lesion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…2,6,12,19 In almost half of the cases of bacterial pneumonia diagnosed in this study, secondary ocular involvement was observed, with features similar to the lesions described in the literature. 6,12,19…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…2,6,12,19 In almost half of the cases of bacterial pneumonia diagnosed in this study, secondary ocular involvement was observed, with features similar to the lesions described in the literature. 6,12,19…”
Section: Discussionsupporting
confidence: 83%
“…Bacterial diseases in several organs can result in ocular lesions secondary to septicemia in humans and animals, and this is often characterized by uveitis. 2,6,12,19 In almost half of the cases of bacterial pneumonia diagnosed in this study, secondary ocular involvement was observed, with features similar to the lesions described in the literature. 6,12,19…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the case described here, the dog showed only bilateral uveitis and moderate abdominal pain on palpation. Uveitis has been reported to develop as a result of bacteremia or septicemia from any local or generalized infectious process …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, uveitis was diagnosed in six bitches. Uveitis has not previously been associated with pyometra but has been described in dogs and cats suffering from severe bacterial infection [ 29 , 30 ]. Cardiac arrhythmia, as identified in five bitches, could have been induced by endotoxemia or myocardial injury [ 21 , 31 ].…”
Section: Discussionmentioning
confidence: 99%